A Tríplice Hélice no contexto da Ciência da Informação: construindo pontes para a Inovação Social - Silva, Liniker Matheus de Sousa (Universidade Federal de São Carlos, 2024)
The evolution of the Triple Helix model, which highlights the collaboration between universities, industry, and government in driving innovation, has been a focus of extensive research and debate in the scientific literature. The present study aims to analyze the contributions of Information Science (IS) to the Triple Helix model, with a focus on the theme of social innovation, identifying the implementation phases of the model, the configurations of relationships established between the three vertices over time, the roles of information in these interactions, and the main challenges encountered. Adopting a qualitative, exploratory, and descriptive approach, this study investigates the institutional approach to the term "Innovation" and its corresponding academic production, by analyzing the scientific production contained in the main database of Information Science, the Base de Dados Referenciais de Artigos de Periódicos em Ciência da Informação (BRAPCI), together with the repositories Base de Teses e Dissertações (BDTD) and the Catálogo de Teses e Dissertações da CAPES. This mapping provided a comprehensive view of the implementation phases of the Triple Helix model, the evolutionary configurations of institutional relationships, the critical role of information, and the main obstacles faced. With these analyses, the work offers points of reflection for strengthening social innovation through inter-sectoral integration, contributing to the development of more effective public policies and the stimulation of strategic partnerships focused on innovation, highlighting the importance of social innovation as a vehicle to meet social needs and promote significant changes through collaboration between the university, industry, and government sectors.
The Triple Helix in the context of Information Science: building bridges for Social Innovation
Keywords: Tríplice hélice; Ciência da informação; Inovação social; Triple helix; Information science; Social innovation; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::TEORIA DA INFORMACAO